How Leaders Can Optimize Teams' Emotional Landscapes - Bradley, Christina (MIT Sloan Management Review, 2021)
Within a workplace, emotional landscapes - the collective composition of employee sentiments - directly influence how people make sense of situations. Managing these landscapes can help in the pursuit of organizational strategic objectives. Current advice recommends strategies such as encouraging general suppression of emotions or giving generic pep talks. Instead, leaders need to respond to employees' emotional states with more nuance.